Simultaneous partial nitrification and 2-fluorophenol biodegradation with aerobic granular biomass: reactor performance and microbial communities - Ramos, Carlos (2017)
An aerobic granular bioreactor was operated for over 4months, treating a synthetic wastewater with a high ammonium content (100mgNL-1). The inoculum was collected from a bioreactor performing simultaneous partial nitrification and aromatic compounds biodegradation. From day-56 onwards, 2-fluorophenol (2-FP) (12.4mgL-1) was added to the feeding wastewater and the system was bioaugmented with a 2-FP degrading bacteria (Rhodococcus sp. FP1). By the end of operation, complete 2-FP biodegradation and partial nitrification were simultaneously achieved. Aerobic granules remained stable over time. During the 2-FP loading, a shift in the community structure occurred, coinciding with the improvement of 2-FP degradation. DGGE analysis did not allow to infer on the bioaugmented strain presence but pyrosequencing analysis detected Rhodococcus genus by the end of operation. Together with other potential phenolic-degraders within granules, these microorganisms were probably responsible for 2-FP degradation.